Sistem Pendukung Keputusan Penentuan Kebijakan Strategi Promosi Kampus Dengan Metode Weighted Aggregated Sum Product Assesment (WASPAS) - Sugiarti, Sri; Nahulae, Dormauli K; Syafrizal, Syafrizal; Panggabean, Tongam E; Sianturi, Maringan (Universitas Budi Darma, 2018)
Decision support system is an application used to facilitate campus promotion team members to determine the strategy policy that will be used in the campus promotion process. This author discusses Decision Support System policy determination campus promotion strategy with WASPAS method. The WASPAS method to be used in this decision support system aims to facilitate the campus promotion team to make good and wise decisions. One of the supporting problems faced by STMIK Budi Darma is the process of determining the location of promotion. From the results of interviews with teams from the field of cooperation, business and marketing STMIK Budi Darma found that the problem of promotion on STMIK Budi Darma because it has not had the right way to choose an effective way to choose a potential school. This potential school can be interpreted as a school that has good financial and academic. To achieve and answer these things one of them can be solved by WASPAS method.